2022
DOI: 10.3389/fpls.2022.949672
|View full text |Cite
|
Sign up to set email alerts
|

Root hair growth from the pH point of view

Abstract: Root hairs are tubular outgrowths of epidermal cells that increase the root surface area and thereby make the root more efficient at absorbing water and nutrients. Their expansion is limited to the root hair apex, where growth is reported to take place in a pulsating manner. These growth pulses coincide with oscillations of the apoplastic and cytosolic pH in a similar way as has been reported for pollen tubes. Likewise, the concentrations of apoplastic reactive oxygen species (ROS) and cytoplasmic Ca2+ oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…It should however be cautioned that root-hair growth and development are highly sensitive to a variety of environmental and hormonal constraints such as water, nutrients and oxygen availability, mechanical perturbations, pH and ROS status, exposure to ethylene, etc. [ 76 , 77 , 78 ]. Importantly, the hardware and experimental designs used in the Arabidopsis study discussed in reference [ 14 ] and our Brachypodium experiment differ significantly in several respects.…”
Section: Resultsmentioning
confidence: 99%
“…It should however be cautioned that root-hair growth and development are highly sensitive to a variety of environmental and hormonal constraints such as water, nutrients and oxygen availability, mechanical perturbations, pH and ROS status, exposure to ethylene, etc. [ 76 , 77 , 78 ]. Importantly, the hardware and experimental designs used in the Arabidopsis study discussed in reference [ 14 ] and our Brachypodium experiment differ significantly in several respects.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the dissolution occurred in acidic conditions and was more pronounced at lower pH. Therefore, a relatively low pH of 4.0 was selected for the mechanistic investigation in the following sections, as this pH range can be found in specialized regions of the plants, e.g., the pectin layer of the fruit and root hairs …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a relatively low pH of 4.0 was selected for the mechanistic investigation in the following sections, as this pH range can be found in specialized regions of the plants, e.g., the pectin layer of the fruit and root hairs. 51 After an extended period of irradiation following the initial 74 h, we noted that Ce 3+ concentration at pH 4.0 gradually decreased to undetectable (Figure 4b). Correspondingly, the peak of Ce 3+ in the UV−vis spectra reached its maximum at 74 h and then became flattened with the appearance of a new peak between 270 and 300 nm, which could be assigned to Ce(IV) (Figure S8b) and suggested the reoxidation of Ce 3+ .…”
Section: Synthesis and Characterization Of Ceo 2 Nanoparticlesmentioning
confidence: 89%
“…Oscillations in growth and cytosolic Ca 2+ fluxes of pollen tube tips [31,32] and root hairs [33] suggest a fundamental growth oscillator; but what activates the oscillator to initiate these oscillations? The pinball model identifies the proton pump as a prime candidate triggered by auxin and mechanostress.…”
Section: Origin Of Growth Oscillations and Ion Fluxesmentioning
confidence: 99%